Upconversion nanoparticles and its based photodynamic therapy for antibacterial applications: A state-of-the-art review - Lv, Hanlin; Liu, Jie; Wang, Ying; Xia, Xiaomin; Li, Ying; Hou, Wenxue; Li, Feng; Guo, Lantian; Li, Xue (Frontiers in Chemistry, 2022)
Major medical advances in antibiotics for infectious diseases have dramatically improved the quality of life and greatly increased life expectancy. Nevertheless, the widespread and inappropriate exploitation of antibacterial agents has resulted in the emergence of multi-drug-resistant bacteria (MDR). Consequently, the study of new drugs for the treatment of diseases associated with multi-drug-resistant bacteria and the development of new treatments are urgently needed. Inspiringly, due to the advantages of a wide antimicrobial spectrum, fast sterilization, low resistance, and little damage to host tissues and normal flora, antibacterial photodynamic therapy (APDT), which is based on the interaction between light and a nontoxic photosensitizer (PS) concentrated at the lesion site to generate reactive oxygen species (ROS), has become one of the most promising antibacterial strategies. Recently, a burgeoning APDT based on a variety of upconversion nanoparticles (UCNPs) such as PS and near-infrared (NIR) light has been fully integrated in antibacterial applications and achieved excellent performances. Meanwhile, conjugated nanoparticles have been frequently reported in UCNP design, including surface-modified PS conjugates, antibiotic-PS conjugates, and dual or multiple antibacterial modal PS conjugates. This article provides an overview of the state-of-the-art design and bactericidal effects of UCNPs and their based APDTs. The first part discusses the design and mechanisms for UCNPs currently implemented in biomedicine. The second part focuses on the applications and antimicrobial effects of diverse APDT based on UCNPs in antibacterial-related infectious diseases.